Effect of cooling procedure on final denture base adaptation - Ganzarolli, S. M.; Rached, R. N.; Garcia, RCMR; Del Bel Cury, A. A. (Blackwell Publishing, 2002)
Well-fitted dentures prevent hyperplasic lesions, provide chewing efficiency and promote patient's comfort. Several factors may affect final adaptation of dentures, as the type of the acrylic resin, the flask cooling procedure and the water uptake. This investigation evaluated the effect of water storage and two different cooling procedures [bench cooling (BC) for 2 h; running water (RW) at 20 degreesC for 45 min] on the final adaptation of denture bases. A heat-cured acrylic resin (CL, Classico, Classico Artigos Odontologicos) and two microwave-cured acrylic resins [Acron MC, (AC) GC Dent. Ind. Corp.; Onda Cryl (OC), Classico Artigos Odontologicos] were used to make the bases. Adaptation was assessed by measuring the weight of an intervening layer of silicone impression material between the base and the master die. Data was submitted to ANOVA and Tukey's test (0.05). The following means were found: (BC) CL=0.72 +/- 0.03 a; AC=0.70 +/- 0.03 b; OC=0.76 +/- 0.04 c//(RW) CL= 1.00 +/- 0.11 a; AC=1.00 +/- 0.12 a; OC=0.95 +/- 0.10 a. Different labels join groups that are not statistically different (P > 0.05). Comparisons are made among groups submitted to the same cooling procedure (BC or RW). The conclusions are: interaction of type of material and cooling procedure had a statistically significant effect on the final adaptation of the denture bases (P < 0.05); water storage was not detected as a source of variance (P > 0.05) on the final adaptation.
Keywords: cooling; denture; acrylic resin; microwave; heat and adaptation